Radiogram from Georg Bredig to Max Bredig, November 21, 1939 - Bredig, Georg (1939)
Georg Bredig (1868-1944) tells his son Max Bredig (1902-1977) that he has accepted the invitation to Princeton University, thus gaining him entry to the United States.
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Emigration and immigration; Chemists; Princeton University; Jewish Holocaust (1939-1945); World War (1939-1945)